Severe fever with thrombocytopenia syndrome-associated encephalopathy/encephalitis. (April 2018) - Park, S.Y.; Kwon, J.-S.; Kim, J.Y.; Kim, S.-M.; Jang, Y.R.; Kim, M.-C.; Cho, O.-H.; Kim, T.; Chong, Y.P.; Lee, S.-O.; Choi, S.-H.; Kim, Y.S.; et al.
Abstract: Objectives: Severe fever with thrombocytopenia syndrome (SFTS) virus has a variety of central nervous system (CNS) manifestations. However, there are limited data regarding SFTS-associated encephalopathy/encephalitis (SFTSAE) and its mechanism. Methods: All patients with confirmed SFTS who underwent cerebrospinal fluid (CSF) examination due to suspected acute encephalopathy were enrolled in three referral hospitals between January 2013 and October 2016. Real-time RT-PCR for SFTS virus and chemokine/cytokines levels from blood and CSF were analysed. Results: Of 41 patients with confirmed SFTS by RT-PCR for SFTS virus using blood samples, 14 (34%) underwent CSF examination due to suspected SFTSAE. All 14 patients with SFTSE revealed normal protein and glucose levels in CSF, and CSF pleocytosis was uncommon (29%, 4/14). Of the eight patients whose CSF was available for further analysis, six (75%) yielded positive results for SFTS virus. Monocyte chemoattractant protein-1 (MCP-1) and interleukin-8 (IL-8) level in CSF were significantly higher than those in serum (geometric mean 1889 pg/mL in CSF versus 264 pg/mL in serum for MCP-1, p = 0.01, and geometric mean 340 pg/mL in CSF versus 71 pg/mL in serum for IL-8, p = 0.004). Conclusions: The CNS manifestation of SFTS as acute encephalopathy/encephalitis is a common complication of SFTS. Although meningeal inflammation was infrequent in patients with SFTSAE, SFTS virus was frequently detected in CSF with elevated MCP-1 and IL-8. These findings indicate that possible direct invasion of the CNS by SFTS virus with the associated elevated cytokine levels in CSF may play an important role in the pathogenesis of SFTSAE.